Why do public firms go private in the UK? The impact of private equity investors, incentive realignment and undervaluation - Renneboog, Luc; Simons, Tomas; Wright, Mike (Journal of Corporate Finance, 2007)
This paper examines the magnitude and the sources of the expected shareholder gains in UK public to private transactions (PTPs) in the second wave from 1997 to 2003. Pre-transaction shareholders on average receive a premium of 40% and the share price reaction to the PTP announcement is about 30%. We test the sources of the anticipated value creation of the delisting and distinguish between: tax benefits, incentive realignment, control reasons, free cash flow reduction, transactions cost reduction, takeover defences, undervaluation and wealth transfers, The main sources of the shareholder wealth gains are undervaluation of the pre-transaction target firm, increased interest tax shields and incentive realignment. An expected reduction of free cash flows does not determine the premiums, nor are PTPs a defensive reaction against a takeover.